Biodegradation of phthalate acid esters by a versatile PAE-degrading strain Rhodococcus sp. LW-XY12 and associated genomic analysis. (May 2022) - Song, Xiaoyong; Zhang, Zihan; Dai, Yanran; Cun, Deshou; Cui, Baihui; Wang, Yuewei; Fan, Yaocheng; Tang, Haibin; Qiu, Liang; Wang, Feihua; Qiu, Dongru; Liang, Wei
Abstract: Di-(2-ethylhexyl) phthalate (DEHP), the most extensively used phthalate acid esters (PAEs), poses a potential risk to human and environment. A novel bacterial strain, Rhodococcus sp. LW-XY12, with efficient PAE-degrading capability, was isolated from activated sludge. Strain LW-XY12 could degrade 96.91 ± 0.68% of DEHP (500 mg L −1 ) within 32 h. The degradation curves of DEHP (50–1500 mg L −1 ) and PAE mixture (500 mg L −1 each) fitted well with the modified Gomperz kinetics model. DEHP metabolic pathway was reconstructed by using genome annotation and metabolic intermediate analyses. The DEHP metabolic pathway might comprise de-esterification and β-oxidation. Homologous modeling and molecular docking analysis revealed that DEHP and MEHP (mono-(2-ethylhexyl) phthalate) could be bound to putative carboxylesterase (KXC42_04905) via hydrogen bonding and hydrophobic interaction. A conserved catalytic triad (Ser195-Glu319-His412) might act as an active protein pocket and catalyze the hydrolysis of DEHP. Carboxylesterase (KXC42_04905) could hydrolyze ester bond and a possible mechanism underlying ester bond hydrolysis catalyzed by the carboxylesterase was proposed. Protocatechuate 3, 4-dioxygenase, 3-oxoadipate CoA-transferase, benzoate 1, 2-dioxygenase, catechol 1, 2-dioxygenase, and catechol 2, 3-dioxygenase transcripts were detected and significantly up-regulated under DEHP induction. This study sheds light on the functional genes associated with DEHP degradation and metabolic mechanism in this versatile bacterium for degradation of PAEs. Graphical abstract: Image 1 Highlights: Strain Rhodococcus sp. LW-XY12 degraded DEHP and other PAE homologs efficiently. DEHP and PAE mixture degradation curves fitted well with the modified Gompertz model. Interactions between a carboxylesterase and DEHP and underlying mechanism were explored. Strain LW-XY12 may degrade catechol through ortho- and/or meta-cleavage pathways. DEHP metabolism pathway was reconstructed by metabolite analyses and genomic annotation.